2005
DOI: 10.1016/j.jcat.2005.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Microkinetic modelling of the dehydrogenation of ethylbenzene to styrene over unpromoted iron oxides

Abstract: A vast amount of surface science experiments provides a detailed qualitative picture of the mechanisms governing the catalytic dehydrogenation of ethylbenzene (EB) to Styrene (St) over unpromoted iron oxide. Also values of kinetic and energetic parameters for adsorption and desorption are available. We present a methodology of kinetic modelling based upon this knowledge, aiming at an accurate prediction of the behaviour of the technical catalysts including deactivation and regeneration. This paper contains the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Concerning the mechanism of catalytic dehydrogenation of ethylbenzene to styrene over iron oxides this is a remarkable result. In model catalysis experiments over Fe 2 O 3 [4,35] it was found that the H formed on the surface reduces the catalyst to Fe 3 O 4 . However, the produced amount of styrene and thus also of hydrogen was by about two orders of magnitude higher than explainable by a stoichiometric reduction reaction with oxygen from the catalyst.…”
Section: H At On Feo(111) -Discussionmentioning
confidence: 99%
“…Concerning the mechanism of catalytic dehydrogenation of ethylbenzene to styrene over iron oxides this is a remarkable result. In model catalysis experiments over Fe 2 O 3 [4,35] it was found that the H formed on the surface reduces the catalyst to Fe 3 O 4 . However, the produced amount of styrene and thus also of hydrogen was by about two orders of magnitude higher than explainable by a stoichiometric reduction reaction with oxygen from the catalyst.…”
Section: H At On Feo(111) -Discussionmentioning
confidence: 99%
“…The depth of the qualitative and quantitative insight already gained was used to design a microkinetic model177 of the reaction based on experimental observations. In contrast to earlier attempts that followed the approach given above with an active center of unspecified nature, in this study a model of a catalyst is used that boasts both oxidic as well as carbon‐based active centers with the generation of these active centers explicitly taken into account.…”
Section: Case Study Of the Dehydrogenation Of Ethylbenzene Over Irmentioning
confidence: 99%
“…Iron (hydr)oxides have been widely used as catalysts in various heterogeneous catalytic processes such as Haber-Bosch to produce ammonia (Bogdanov et al, 1990;Holme, 1997), the Fischer-Tropsch hydrocarbon synthesis (Moodley et al, 2010;Dong et al, 2011;, steam reforming (Matsuoka et al, 2006;Gong et al, 2009), water-gas shift (Basinska et al, 2006;Datta et al, 2011), ethylbenzene dehydro-genation to produce styrene monomers (Schüle et al, 2005;Li & Shanks, 2011), water splitting for hydrogen production (Lin et al, 2011;Pereira et al, 2011a), aerobic oxidation of organic compounds to produce new products for the fine chemical industry (Menini et al, 2008(Menini et al, , 2011 and in advanced oxidation processes (AOPs) to oxidize pollutants in water and soils (He et al, 2002;Andrade et al, 2009;Silva et al, 2009;Botas et al, 2010;Hu et al, 2011;Rodriguez et al, 2011;Sreethawong & Chavadej, 2011;Vicente et al, 2011).…”
mentioning
confidence: 99%